Moderasi Beragama dalam Perspektif Al-Qur’an dan Bibel - Arifinsyah Arifinsyah; M. Fatahillah Al Huzaify; Fitri Huril Aini; Ayu Ulfa Mahdani Saragih; Rohilah Rohilah (PKP Pusat Jurnal LPPM IAi Nasional Laaroiba, 2023)
Indonesia is a plural country consisting of different tribes, races and religions, so tolerance is needed in understanding all the differences that exist, including Indonesian society, which incidentally is diverse. Therefore, religious moderation is very appropriate to be applied in the life of the nation and state, especially in people who adhere to Islam and Christianity because they are the majority religion. This study tries to examine the concept of religious moderation, moderation in the perspective of the Qur'an and the Bible, and the application of religious moderation in the perspective of the Koran and the Bible. The research methodology uses a literature study by analyzing various existing literature sources. The results of this study indicate that religious moderation is a balanced religious attitude in practicing one's own religion and respecting and appreciating the religious practices of other people of different beliefs, which is absolutely necessary in Indonesia to reduce various phenomena of intolerance. Keywords: Religious moderation, Al-Qur'an, Bible, Society.